1999
DOI: 10.1364/ao.38.007018
|View full text |Cite
|
Sign up to set email alerts
|

Generalized algorithm for photoelastic measurements based on phase-stepping imaging polarimetry

Abstract: A general method for measuring the birefringence of nondichroic, linear retarder media has been presented. The method is based on phase-stepping imaging polarimetry and permits the azimuth angle, phase retardation, and transmission coefficient of a sample to be calculated. The method uses a simple setup, a sample at rest, and permits fast acquisition of data. With the mathematical description applied, various algorithms for different optical configurations can be used and any number of intensity patterns can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…Van Blokland and Verhelst reported that although there is a large variability among subjects, the corneal retardation is non-null and approximately constant at the central area of the pupil plane (558 on average) and increases with eccentricity (for some subjects larger that 2008). Jaronski and Kasprzak (1999) also found an increase in retardation by but they did not report numerical values. Our results show only a slight increase along the radius.…”
Section: Discussionmentioning
confidence: 92%
“…Van Blokland and Verhelst reported that although there is a large variability among subjects, the corneal retardation is non-null and approximately constant at the central area of the pupil plane (558 on average) and increases with eccentricity (for some subjects larger that 2008). Jaronski and Kasprzak (1999) also found an increase in retardation by but they did not report numerical values. Our results show only a slight increase along the radius.…”
Section: Discussionmentioning
confidence: 92%
“…19 Jaronski and Kasprzak devised a phase stepping imaging polarimetry technique to measure the birefringence of human cornea in vitro, and concluded that corneal birefringence increases monotonically in the direction of the corneal periphery. 20,23 Hitzenberger, Gotzinger and Pircher employed polarization sensitive optical coherence tomography to map the distribution of birefringence at the posterior corneal surface. 21 Their results indicated that birefringence is low for beams incident normal to the corneal surface, and that at oblique angles, measured birefringence increases with deviation from normal incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas in some areas the angle is positive, in others it is clearly negative, with a variable pattern. The azimuth for the whole eye, and the retina and the cornea themselves has been measured by different authors (Kaplan and Bettelheim, 1972; Bour and Lopes Cardozo, 1981; van Blokland and Verhelst, 1987; klein Brink and van Blokland, 1988; Pelz et al ., 1996; Jaronski and Kasprzak, 1999; Bueno, 2000; Bueno and Jaronski, 2001). To our knowledge this paper presents the first results of a spatially resolved lenticular azimuth.…”
Section: Discussionmentioning
confidence: 99%